Guided local search for query reformulation using weight propagation - Moghrabi, Issam (Zielona Góra: Uniwersytet Zielonogórski)
A new technique for query reformulation that assesses the relevance of retrieved documents using weight propagation is proposed. The technique uses a Guided Local Search (GLS) in conjunction with the latent semantic indexing model (to semantically cluster documents together) and Lexical Matching (LM).
Keywords: relevance feedback; clustering; latent semantic; query reformulation